FARMERS ENTREPRENEURIAL COMPETENCIES AND TECHNICAL EFFICIENCY OF RICE FARMS - Olubunmi Lawrence BALOGUN (Slovak University of Agriculture, 2021)
Research background: Rice (Oriza sativa) is a staple food in most homes in Nigeria, its demand has not been able to cope favourably well with the production. Efforts to develop and improve the production of the crop in the country were seriously curtailed due to inefficiency in the use of available resources. Purpose of the article: The study set to determine the effects of farmers’ entrepreneurial competencies (ECs) on technical efficiency (TE) of rice farms in South-west, Nigeria. Also, the study was trying to profile the socioeconomic characteristics of rice farmers and identifying their ECs in order to describe the determinants of technical efficiency of rice farms. Methods: A multistage sampling technique was employed to select 504 respondents from which information on their socioeconomic characteristics, their ECS’ variables and input-output variables were collected. The information gathered were analysed using descriptive statistics and stochastic frontier production (SFP) function (Cobb-Douglas model). Findings & value added: The results showed that farms were technically inefficient with a mean TE score of 0.6842 with evidence of increasing returns to scale. The results of the Maximum-likelihood Estimation of the SFP model reveals that the quantity of seed planted, farm size and amount of man-day labour used significantly explained the technical efficiency of rice farms. Also, some socioeconomic factors and ECs factors such as organising and commitment were found to be responsible for rice farmers’ inefficiency. The study recommends appropriate entrepreneurial training for rice farmers focussing on resource management and training the extension workers on necessary competency knowledge.